Kontestasi Aktor dan Model Kolaboratif Pemberdayaan Orang Rimba di Taman Nasional Bukit Duabelas Provinsi Jambi - Muchlis, Fuad; Sardi, Idris (Sodality: Jurnal Sosiologi Pedesaan, 2022)
The empowerment of the Orang Rimba aims to enable them to get out of their marginal condition due to the development pattern that has not been on their side so far. This study aims to analyze how the contestation of various ideologies underlie various actors empowering the Orang Rimba and to formulate a collaborative model between actors in empowerment that can answer the needs of the Orang Rimba. The research uses a case study approach and is analyzed qualitatively. The results show that the empowerment of Orang Rimba is interpreted by the state as "modernization" by means of resettlement, using an economical approach as an indicator of the success of a program. NGOs interpret empowerment as building critical awareness by providing alternative education and advocacy, while Corporations empower them through CSR activities. Multi-stakeholder collaboration for empowerment can be carried out by utilizing a forum or Multi-stakeholder Cooperation Forum for the Empowerment of Orang Rimba. The multi-stakeholder collaborative model of empowerment through state facilitation, NGOs, and corporations has a common goal of increasing dignity and independence following the needs and socio-cultural conditions of the Orang Rimba.